The Role of Market Orientation on the Relationship between Total Quality Management Dimensions and Organizational Performance: A Study on Banks in Libya - Ahmed Faiz, Gaboul (Journal of Advanced Research in Business and Management Studies, 2020)
The main purpose of this study was to examine the mediating effect of Market Orientation (MO) on the relationship between Total Quality Management (TQM) dimensions namely :( management leadership, customer focus, and continuous improvement) and Organizational Performance (OP). Due to inconsistency in the previous literature, a management tool needed to play the role as a mechanism that can explain the relationship between TQM dimensions and organizational performance in better way. Therefore, this study tried to introduce market orientation as the mechanism between TQM dimensions and organizational performance. Questionnaires were distributed to 400 branches of the Libyan banks. 230 questionnaires were returned and used in the analysis using the PLS-SEM. The results of this study revealed that TQM was positive and have also been proven to be significant predictors of organizational performance. More importantly, the results have also confirmed the mediating effect of Market Orientation on the relationships between TQM dimensions, and organizational performance.